(untitled) (Indian Journal of Animal Production and Management, 2015)
The study was carried out in Sabarkantha district of Gujarat to identify the various constraints perceived by the farmers in adoption of dairy animal management practices. A random sample of 100 farmers were selected from 5 talukas of the district and the constraints in adoption of management practices in aspect of housing, feeding, breeding, milking & health care management practices were studied. The result of study depicted that lack of knowledge of cheap and scientific housing, lack of knowledge for efficient utilization of feed and fodder, lack of knowledge for feeding mineral mixture, poor result of Artificial Insemination, repeat breeding, lack of knowledge about scientific method of milking and lack of knowledge to control ectoparasite were constraints perceived by the farmers.